2021
DOI: 10.1002/chem.202100328
|View full text |Cite
|
Sign up to set email alerts
|

Altered Membrane Mechanics Provides a Receptor‐Independent Pathway for Serotonin Action

Abstract: Serotonin, an importants ignalingm olecule in humans, has an unexpectedly high lipid membrane affinity. The significance of this finding has evokedc onsiderable speculation. Here we show that membrane binding by serotonin can directly modulate membrane properties and cellular function, providing an activity pathway completelyi ndependent of serotonin receptors. Atomic force microscopy shows that serotonin makes artificial lipid bilayers softer,a nd inducesn ucleation of liquid disordered domains inside the raf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 73 publications
3
53
0
Order By: Relevance
“…Tryptophan [376][377][378], Glycine [139,284], Glutamate [139], Aginine [379], Alanine [379], 5-aminolevulinic acid and its esters [380], L-dopa [138,199,381,382] Nucleotides ATP [383], UMP [384], DNA [385], ADOMET [381] Sugars and carbohydrates Trehalose [386], Gastrodin [387], Mannitol [199], 1,3,7-trimethyluric acid [388] Neurotransmitters Dopamine [138,[389][390][391][392][393][394][395][396][397], Serotonin [138,378,389,396,[398][399][400][401][402], Adenosine [138], Melatonin [138,229,378,389,[403][404]…”
Section: Antioxidantsmentioning
confidence: 99%
“…Tryptophan [376][377][378], Glycine [139,284], Glutamate [139], Aginine [379], Alanine [379], 5-aminolevulinic acid and its esters [380], L-dopa [138,199,381,382] Nucleotides ATP [383], UMP [384], DNA [385], ADOMET [381] Sugars and carbohydrates Trehalose [386], Gastrodin [387], Mannitol [199], 1,3,7-trimethyluric acid [388] Neurotransmitters Dopamine [138,[389][390][391][392][393][394][395][396][397], Serotonin [138,378,389,396,[398][399][400][401][402], Adenosine [138], Melatonin [138,229,378,389,[403][404]…”
Section: Antioxidantsmentioning
confidence: 99%
“…HepG2 cells only express minimal levels of the serotonin receptors 1A and 1D and the highest level of the serotonin transporter of any human cell line (Human Protein Atlas 48 ). Imipramine and citalopram treatment may enhance Lp(a) surface binding by inhibiting the serotonin transporter, allowing accumulation of extracellular serotonin and inducing membrane changes as observed by Dey et al 47 .…”
Section: Resultsmentioning
confidence: 89%
“…Serotonin transporter inhibition prevents serotonin uptake from the extracellular space 46 , leading to elevated extracellular serotonin levels. Interestingly, a recent study found addition of exogenous serotonin to cells enhances transferrin cell surface binding and subsequent endocytosis by altering the physical properties of the plasma membrane independent of serotonin receptors or transporter 47 . HepG2 cells only express minimal levels of the serotonin receptors 1A and 1D and the highest level of the serotonin transporter of any human cell line (Human Protein Atlas 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small transmitters directly interact with membranes and can be broadly divided into two groups. Lipophilic transmitters (i.e., melatonin, serotonin, histamine, dopamine, noradrenaline, adrenaline, and adenosine) had high lipid partition coefficients (Wang et al, 2011 ; Postila et al, 2016 ; Engberg et al, 2020 ; Josey et al, 2020 ; Parkkila and Viitala, 2020 ) and can operate in receptor-independent mechanisms by changing lipid dynamics (Dey et al, 2021 ). They accumulated within surface membrane layers (e.g., postsynaptic membranes) with enhanced planar 2D diffusions.…”
Section: Endoplasmic Reticulum In Protoneuronal Secretory Cells Might Promote Synaptogenesis In Evolutionmentioning
confidence: 99%